2019
DOI: 10.3390/s19225038
|View full text |Cite
|
Sign up to set email alerts
|

Compact Inner-Wall Grating Slot Microring Resonator for Label-Free Sensing

Abstract: In this paper, we present and analyze a compact inner-wall grating slot microring resonator (IG-SMRR) with the footprint of less than 13 μm × 13 μm on the silicon-on-insulator (SOI) platform for label-free sensing, which comprises a slot microring resonator (SMRR) and inner-wall grating (IG). Its detection range is significantly enhanced without the limitation of the free spectral region (FSR) owing to the combination of SMRR and IG. The IG-SMRR has an ultra-large quasi-FSR of 84.5 nm as the detection range, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Coupling the light from w=450nm wide straight waveguide to the MRR resonator a q-factor of as high as 17900 is observed. It should be noted that although this value is much higher than previous study (Gu et al, 2019), this can be a guideline for future studies to model the sensor with the optimal values.…”
Section: − = (1)mentioning
confidence: 77%
See 1 more Smart Citation
“…Coupling the light from w=450nm wide straight waveguide to the MRR resonator a q-factor of as high as 17900 is observed. It should be noted that although this value is much higher than previous study (Gu et al, 2019), this can be a guideline for future studies to model the sensor with the optimal values.…”
Section: − = (1)mentioning
confidence: 77%
“…In order to increase the sensitivity, different geometries have been utilized (Yuan et al, 2014;De Vos et al, 2017). Among them, employing a double-slot geometry it is possible to obtain a sensitivity of as high as 560 nm/RIU, as well as a quality factor of 1020 with the footprint of less than 13μm X 13μm (Gu et al, 2019). Even though slot-sensors offer high sensitivity, they experience high optical losses that directly affect the quality factor (Steglich et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the slot waveguide has been demonstrated that there is a larger electric field distributing in the low refractive index material, which owns stronger the interaction between light and matter than the strip waveguide. To obtain high sensitivity, a slot microring resonator with period inner walls was proposed, which achieved a high sensitivity of 559 nm/RIU and a large FSR of 83 nm [8]. Higher sensitivity filter designed by the subwavelength grating microring resonator (SWGMRR) with period inner angular gratings was subsequently demonstrated to obtain a sensitivity of 672.8 nm/RIU [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various structures of MRR sensors have been developed to improve their sensitivity. For example, a one-dimensional photonic crystal MRR with periodic air holes is introduced in a microring waveguide [20][21][22], grating-type MRR [23][24][25], and SMRR [26][27][28][29][30][31][32]. The SMRR introduces an air slot in microring waveguides, where the evanescent field of each individual silicon brick is extremely high, constructively guiding the quasi-TE mode into the slot region to interact with the matter [26].…”
Section: Introductionmentioning
confidence: 99%